(untitled) (Research, Society and Development, 2020)
Introduction: Pressure ulcers are lesions in the skin or in the underlying tissue caused by long periods of immobility, local ischemia occurs and, as a consequence, tissue death. It is considered a worldwide public health problem. Low-level laser therapy is used copiously in the treatment of pressure ulcers. Objective: The objective of this work is to carry out a systematic review about the effect of low-level laser on the tissue repair process in patients with pressure ulcers. Methodology: Systematic literature review of articles selected from the pubmed, Periódicos Capes, BVS Brasil and Google academic databases. The Descriptors (Decs) were: Laser therapy, low intensity light therapy and Pressure ulcers. The keywords were crossed between inserted in quotation marks for screening the search. PICO strategy was adopted. Inclusion criteria were articles from the past ten years in human patients in English and Portuguese. Articles that did not comply with the inclusion criteria were discarded. Results: Most articles point out that the low intensity laser promotes better results in the healing process of pressure ulcers. Conclusion: From the selected studies, it was observed that the wavelengths of 658 and 660nm achieved better results in the healing process of pressure ulcers.